The Role of Grammar to Enhance Accuracy and Fluency in EFL Teaching - Pereira Loor, Josceline Michell; Guevara Peñaranda, Ninfa Sofia (Arandu UTIC, 2025)
The study examines the impact of explicit grammar instruction on enhancing both accuracy and fluency in English as a Foreign Language (EFL) students in Ecuador. Despite national educational efforts, English proficiency in Ecuador remains low, particularly in productive skills like speaking and writing. The study argues that explicit grammar teaching and communicative practice are necessary for improving these skills. Using a mixed-methods approach, 50 undergraduate students participated in grammar instruction over 14 weeks. Results showed significant improvements in grammatical accuracy, such as reduced errors related to verb conjugation, articles, and sentence structuring. Fluency also increased, with more coherent and natural written production. These findings suggest that grammar teaching integrated with real-life communication enhances both accuracy and fluency. The study recommends continued use of this integrated approach for improving EFL proficiency and calls for further research with larger samples and over extended periods.